Posterior approaches to the ankle – an analysis of 3 approaches for access to the posterior malleolar fracture. (December 2020) - Philpott, Matthew D.G.; Jayatilaka, Malwattage Lara Tania; Millward, Graham; Molloy, Andrew; Mason, Lyndon
Highlights: The surface area exposure was significantly greater in the posteromedial and medial posteromedial approach as compared to the posterolateral approach. When comparing the fracture width to the approach, no approach achieves a complete exposure of the type 2B or 3 fracture patterns. Considering the lateral to medial extent of the fracture, the posterolateral fragment mean width is 33% greater than what can be exposed by the posterolateral approach (mean 24.9 vs 16.8 mm). The PM approach exposes 47.6% of the type 2B fracture pattern and 57.1% of the type 3 fracture pattern and allows a preferable angle for hardware insertion. The MPM approach does not expose any of the posterolateral fragments in this study, however it does expose 92% (mean 21.9 vs. 23.8 mm) of the medial to lateral width of a posteromedial fragment of a type 2B fracture. Abstract: Background: An anatomical study to determine what degree of access to the posterior distal tibia could be gained by using 3 different approaches; the posterolateral, the posteromedial and the medial posteromedial approaches. Methods: A comparison study, between the anatomical dissection of 7 fresh frozen cadaveric lower legs and image analysis of CT data of posterior malleolar fractures from a prospectively collected database was conducted. All fractures have been classified using the Mason and Molloy classification. Results: In comparing the posterior malleolar fracture fragment width to distal tibia width, the posterolateral fragment encompasses 60.1% (95% CI 56.8, 63.3) of the total width of the tibia. If the posteromedial fragment is included the fragments encompass the entire distal tibia (100%). In type 3 fractures, 81.4% (95% CI 75.5, 87.1) of the distal tibia width is involved. When comparing the fracture width to the approach, no approach achieves a complete exposure of the type 2B or 3 fracture patterns. The overall surface area of the type 2B and 3 fractures, is significantly greater than all the approaches. Considering the lateral to medial extent of the fracture, the posterolateral fragment mean width is 33% greater than what can be exposed by the posterolateral approach (mean 24.9 vs 16.8 mm). In type 2B and 3 fractures, the horizontal exposure reduces to 39.8% and 47.6% respectively. In comparison, the PM approach exposes 47.6% of the type 2B fracture pattern and 57.1% of the type 3 fracture pattern and allows a preferable angle for hardware insertion. The MPM approach does not expose any of the posterolateral fragments in this study, however it does expose 92% (mean 21.9 vs. 23.8 mm) of the medial to lateral width of a posteromedial fragment of a type 2B fracture. Conclusion: Each approach allows access to different parts and amounts of the posterior tibia. An understanding of and utilisation of these approaches can lead to adequate exposure for fixation of most posterior malleolus fracture patterns seen.